Diversion and injection of buprenorphine–naloxone film two years post‐introduction in Australia. (9th October 2015) - Larance, Briony; Mattick, Richard; Ali, Robert; Lintzeris, Nicholas; Jenkinson, Rebecca; White, Nancy; Kihas, Ivana; Cassidy, Rosemary; Degenhardt, Louisa
Abstract: Introduction and Aims: We report 2 years of post‐marketing surveillance of the diversion and injection of buprenorphine–naloxone (BNX) film following its introduction in 2011. Design and Methods: Interviews were conducted with people who inject drugs regularly (PWID) (2004–2013), opioid substitution therapy clients (2013, n = 492) and key experts ( n = 44). Key outcomes were unsanctioned removal of supervised doses, diversion, injection and street price. Prevalence of past 6‐month injection among PWID was adjusted for background availability of opioid substitution therapy medications using sales data. Results: Among out‐of‐treatment PWID, the levels of regular (weekly+) BNX film injection were comparable to methadone and BNX tablets, and lower than mono‐buprenorphine, adjusting for background availability. Fewer BNX film clients [3%; 95% (CI) 1–5] regularly injected their medication than mono‐buprenorphine clients (25%; 95% CI 11–39), but at levels equivalent to those among methadone (3%; 95% CI 1–6) and BNX tablet clients (2%; 95% CI 0–6). Key experts perceived BNX film needed less supervised dosing time as it dissolved rapidly and was harder to remove from the mouth than sublingual tablets; however, removal of supervised doses was higher among BNX film clients (15%; 95% CI: 10–20) than methadone clients (3%; 95% CI 1–6), and not significantly different from BNX tablet (11%; 95% CI 2–21) and mono‐buprenorphine clients (31%; 95% CI 16–46). Discussion and Conclusions: Two years post‐introduction, levels of BNX film diversion and injection remained comparable with those for methadone and BNX tablets, and lower than mono‐buprenorphine. We found no evidence that BNX film has lower non‐adherence and diversion than the tablet formulation. [Larance B, Mattick R, Ali R, Lintzeris N, Jenkinson R, White N, Kihas I, Cassidy R, Degenhardt L. Diversion and injection of buprenorphine–naloxone film two years post‐introduction in Australia. Drug Alcohol Rev 2015]